2021
DOI: 10.1155/2021/5535788
|View full text |Cite
|
Sign up to set email alerts
|

miR-129 Attenuates Myocardial Ischemia Reperfusion Injury by Regulating the Expression of PTEN in Rats

Abstract: PTEN/AKT signaling plays pivotal role in myocardial ischemia reperfusion injury (MIRI), and miRNAs are involved in the regulation of AKT signaling. This study was designed to investigate the interaction between miR-129 and PTEN in MIRI. A MIRI rat model and a hypoxia reoxygenation (H/R) H9C2 cell model were constructed to simulate myocardial infarction clinically. TTC staining, creatine kinase (CK) activity, TUNEL/Hoechst double staining, Hoechst staining and flow cytometer were used for evaluating myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Cui et al 28) reported that knocking down PTEN could reduce myocardial pathological damage and inhibit NLRP3-mediated myocardial cell apoptosis. Dai et al 29) reported that miR-129 alleviated MIRI in rats by inhibiting PTEN expression. Through bioinformatics prediction and verification, we noted that miR-761 and PTEN had mutual binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al 28) reported that knocking down PTEN could reduce myocardial pathological damage and inhibit NLRP3-mediated myocardial cell apoptosis. Dai et al 29) reported that miR-129 alleviated MIRI in rats by inhibiting PTEN expression. Through bioinformatics prediction and verification, we noted that miR-761 and PTEN had mutual binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs discussed in this section are listed in the following Table 2. Human HF [183] 1 CHF in rats [178] 2 Keap1 [182] Suppressed transcription of Nrf2-dependent antioxidant genes [96] I/R injury in rodents [179][180][181] AngII-induced CM hypertrophy [182] HMGB1 [180] Enhanced HMGB1-mediated NOX activation and subsequent ROS production [157,158] miR-130…”
Section: Mir-381mentioning
confidence: 99%
“…Previous studies have reported that the expression of miR-129 was down-regulated in various experimental models of CVDs, such as CHF [ 178 ], myocardial I/R injury [ 179 , 180 , 181 ], and Ang II-induced CM hypertrophy [ 182 ]. More recently, the down-regulation of miR-129 in the cardiac tissue of patients with heart failure has also been reported [ 183 ].…”
Section: Differentially Expressed Mirnas In Cvds and Oxidative Stressmentioning
confidence: 99%